Adding the second and the third equations we get:
![\begin{gathered} 3x+y-4z+x-y+3z=10-5, \\ 4x-z=5. \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/gfigqoxwjyx6evcmttynjzgj9l8i24u5ue.png)
Now, adding the first and two times the second equation we get:
![\begin{gathered} -4x+2y+z+2x-2y+6z=1-10, \\ -2x+7z=-9. \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/u5qznym7jvu6tujb1jetoy33kn7zsrybhu.png)
Then, we have the following system of equations:
![\begin{gathered} 4x-z=5, \\ -2x+7z=-9. \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/sj8ib2vheltczbs55kgnaqx6kmnj1o3j1z.png)
Adding the first equation to two times the second equation, and solving for z we get:
![\begin{gathered} 4x-z-4x+14z=5-18, \\ 13z=-13, \\ z=-(13)/(13), \\ z=-1. \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/garxjh8jvtmt0bf69b46ucud8xbhaq81yf.png)
Substituting z=-1 in the first equation of the second system and solving for x we get:
![\begin{gathered} 4x-(-1)=5, \\ 4x=5-1, \\ 4x=4, \\ x=1. \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/s2lktxm1500wum66bsdvwbifb2pu4jynqj.png)
Finally, substituting x=1, z=-1, and solving for y in the first equation of the first system we get:
![\begin{gathered} -4(1)+2y+(-1)=1, \\ -4+2y-1=1, \\ 2y=6, \\ y=(6)/(2), \\ y=3. \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lr3dyq5fmcq85tcxzk24skf5vz7kf6ieia.png)
Answer:
![\begin{gathered} x=1, \\ y=3,\text{ } \\ z=-1. \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/44xpdg6xa9pl6spls2hv8tb2v93nmlrph1.png)